Análisis jurídico sobre la resistencia y derechos vulnerados en el levantamiento y manifestaciones ciudadanas de junio Cantón Puyo año 2022 - Shakai Shimbiucta, Tuntiak Edvar (2023)
The Constitution of the Republic of Ecuador is a guarantee of rights, therefore, according to art. 98 Right to Resistance, the uprising and citizen demonstrations called after analysis by the great Confederation of Indigenous Nationalities of the Ecuadorian Amazon - CONFENIAE, base of the Confederation of Indigenous Organizations of Ecuador - CONAIE, were carried out within various internal agendas and activities carried out in each province of the country, in the city of Puyo, using as a constitutional means of publicizing and expressing their disagreement with the economic and extractivist policies of the Government of Guillermo Lasso, among various issues, the most urgent being the rise in fuel that led carried out indigenous demonstrations (social protests), the same ones that, in turn, took place in the Puyo canton. This investigation is developed from an analytical, interpretive and legal point of view on the causes and prejudicial, judicial effects and constitutional rights that have obviously been violated as a result of exercising the right to resistance in said demonstrations. The legal analysis on the right to resistance in the uprising and demonstrations carried out in the city of Puyo in June 2022 will allow us to determine the violated rights established in the Constitution of the Republic of Ecuador, given that citizens, in the exercise of their individual or collective rights, they are free to demonstrate peacefully, but to what extent will it be admissible to tolerate poverty, unsatisfied needs and the lack of importance specifically towards rural communities. These and other questions will be reflected thanks to surveys, interviews, and all kinds of informational data collection carried out in the population of San Jacinto, both workers, entrepreneurs, farmers, and citizens in general. The methodology used in the study is mixed, through analytical, deductive, bibliographical, and legal research; emphasizing the problem raised from a social perspective, which has served to acquire multiple knowledge regarding the subject, allowing in turn to obtain results that generate a broad and detailed study of the subject addressed and the social problems that it entails, in the same way way to obtain and generate conclusions and recommendations that are expected to be accepted in their entirety, since they will be widely and very useful for future investigations, especially in demonstrating the contradictions and legal loopholes that exist when it comes to stigmatizing and criminalizing demonstrations by of the State. Keywords: Resistance, Rights, Stigmatize, Criminalize